ANALISIS PERLINDUNGAN HUKUM MEREK TERKENAL YANG BELUM TERDAFTAR DI INDONESIA (STUDI KASUS PUTUSAN MAHKAMAH AGUNG NOMOR 790K/PDT.SUS-HKI/2020) - Vanesha Margaretta; Christine S.T. Kansil (Jurnal Hukum Adigama, 2021)
Legal protection at TRIPS and international conventions is basically to protect the existence of well-known brands on an international scale against bad faith by other parties who want to join in and take advantage of these well-known brands. The problem faced is the legal protection of wellknown trademarks that have not been registered in Indonesia in the Supreme Court Decision Number 790 K/Pdt.Sus-HKI/2020. The research method used is normative juridical legal research. Research results show that the protection of well-known brands is primarily regulated in the Paris Convention for the Protection of Industrial Property (“Paris Convention”) and also in the Agreement on Trade-Related Aspects of Intellectual Property Rights (“TRIPS Agreement”). The provisions to protect well-known marks above apply to all member countries of the Paris Convention and signatories to the TRIPS Agreement (the World Trade Organization's TRIPS Agreement). Each member of the World Trade Organization (WTO) is a member of the World Intellectual Property Organization (WIPO), the Paris Convention and the TRIPS Agreement attached to WIPO. So that every member country of WIPO and WTO, including Indonesia, must submit to the two treaties. Government efforts through Trademark Law No. 20 of 2016 concerning Trademarks and Geographical Indications in providing protection against brands in Indonesia is a positive step from the government circles in this case the Directorate General of KI in uncovering every case of trademark disputes.